2007
DOI: 10.1002/micr.20401
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular breast reconstruction pedicle thrombosis: How long can we wait?

Abstract: Re-exploration plays a key role in salvaging vascularly compromised free flaps. A retrospective review of 290 free flaps in breast reconstruction was performed to determine whether the time delay between thrombosis detection and surgical re-exploration had any effect on flap salvage. Overall flap success was 97.6%. Postoperative thrombosis requiring re-exploration was documented in 6.2% cases. Fifty-five percent of take-back flaps were salvaged and 45% were lost. The median time between detection of flap compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…9 -12 Yet even the most methodical surgeon has, to this point, been unable to reduce the risk of flap loss to 0 percent. The most common cause of flap compromise continues to be pedicle thrombosis, which must be addressed in a timely fashion if a flap is to be salvaged.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…9 -12 Yet even the most methodical surgeon has, to this point, been unable to reduce the risk of flap loss to 0 percent. The most common cause of flap compromise continues to be pedicle thrombosis, which must be addressed in a timely fashion if a flap is to be salvaged.…”
Section: Discussionmentioning
confidence: 96%
“…[7][8][9][10] Venous thrombosis is more common than arterial thrombosis, occurring in up to 74 percent of thrombosed flaps, 10 the majority of these complications reportedly occurring within 3 days of the initial operation. To date, no reports have established the incidence of venous thrombosis later in the immediate postoperative period (Ͼ3 days).…”
mentioning
confidence: 99%
“…In a retrospective review of 290 free flaps used for breast reconstruction, Vijan and Tran [23] showed a significant difference in salvage rates between flaps that were reexplored earlier versus later. They observed that flaps taken back to the operating room for reexploration within 128 min postoperatively were salvaged, while those taken back after 228 min failed.…”
Section: Principles Of Antithrombotic Therapy In Microvascular Surgerymentioning
confidence: 99%
“…21,24,27,36 Once thrombosis is recognized, faster return to the operating room predicts salvage. 28 Mirzabeigi and colleagues showed a decline in flap salvage rates over time, including 64 percent at 0 to 48 hours, 46 percent at 49 to 96 hours, and 0 percent at greater than 96 hours. Similar trends have been shown by others.…”
Section: Timing Of Flap Thrombosis and Salvage Ratesmentioning
confidence: 95%
“…24 High-volume centers have published contemporary total flap loss rates of 1.1 to 3.0 percent. [24][25][26][27][28][29] A "threshold" of 70 free flaps has been suggested as the cutoff for the learning curve. 24…”
Section: Rates Of Free Flap Thrombosismentioning
confidence: 99%